ONLINE FORUMS AND SOLICITED BLOGS: INNOVATIVE METHODOLOGIES FOR ONLINE GAMING DATA COLLECTION - GRIFFITHS, MARK D.; LEWIS, ANDREA M.; ORTIZ DE GORTARI, ANGELICA B.; KUSS, DARIA J. (Studia Psychologica: Theoria et praxis, 2015)
Although online data collection has become increasingly common for social scientists working in the field of gaming studies, two of the least used methods in online gaming research are the collection of data from (i) online forums and (ii) solicited online diary blogs. This paper overviews these two innovative data collection methods and examines both the advantages (e.g., ease of data collection; rich and complex resource of textual material that can be revisited after the event; targeting specific and/or diverse populations; participant anonymity; participant convenience; increased honesty, etc.) and disadvantages (e.g., lack of contextual data; sampling bias; lack of researcher control, lack of knowledge about participant behaviour, generalizability) to aid those researchers working in the online gaming studies field. This paper extends upon previous methodological papers in the area by outlining some of the methodological and ethical issues associated with these two specific online methodologies. Although online data collection may raise concerns about the research participants’ integrity and the quality of the data collected, it is concluded that the use of online forums and online solicited diary blogging can provide new insights unavailable to other data collection methods for those working in the gaming studies field.